Digital Light Processing Bioprinted Human Chondrocyte-Laden Poly (γ-Glutamic Acid)/Hyaluronic Acid Bio-Ink towards Cartilage Tissue Engineering - Alvin Kai-Xing Lee; Yen-Hong Lin; Chun-Hao Tsai; Wan-Ting Chang; Tsung-Li Lin; Ming-You Shie (Biomedicines, 2021)
Cartilage injury is the main cause of disability in the United States, and it has been projected that cartilage injury caused by osteoarthritis will affect 30% of the entire United States population by the year 2030. In this study, we modified hyaluronic acid (HA) with γ-poly(glutamic) acid (γ-PGA), both of which are common biomaterials used in cartilage engineering, in an attempt to evaluate them for their potential in promoting cartilage regeneration. As seen from the results, γ-PGA-GMA and HA, with glycidyl methacrylate (GMA) as the photo-crosslinker, could be successfully fabricated while retaining the structural characteristics of γ-PGA and HA. In addition, the storage moduli and loss moduli of the hydrogels were consistent throughout the curing durations. However, it was noted that the modification enhanced the mechanical properties, the swelling equilibrium rate, and cellular proliferation, and significantly improved secretion of cartilage regeneration-related proteins such as glycosaminoglycan (GAG) and type II collagen (Col II). The cartilage tissue proof with Alcian blue further demonstrated that the modification of γ-PGA with HA exhibited suitability for cartilage tissue regeneration and displayed potential for future cartilage tissue engineering applications. This study built on the previous works involving HA and further showed that there are unlimited ways to modify various biomaterials in order to further bring cartilage tissue engineering to the next level.